Systematic review of cochlear implantation in CHARGE syndrome. (3rd September 2019) - Amin, Nikul; Sethukumar, Priya; Pai, Irumee; Rajput, Kaukab; Nash, Robert
Abstract : Objective: CHARGE syndrome presents with a collection of congenital anomalies affecting multiple organs. Ear and temporal bone anomalies, including hearing loss are highly prevalent. We present an aid to management of this challenging condition and report the strategies and outcomes of cochlear implantation. Methods: Systematic review of Medline, EMBASE, Web of Science, CENTRAL and clinicaltrials.gov was performed up to 21/10/2018 The review and meta-analysis of studies were performed according to the PRISMA statement. Patient demographics, comorbidity, anatomical factors, details of cochlear implantation and audiological outcome were extracted and summarized. Anatomical and surgical factors were evaluated by meta-analysis. Audiological outcomes reported were too heterogeneous for meta-analysis. All statistics were calculated with SPSS v23.0 (IBM, New York, USA). Results: Thirty-one studies reported 165 cochlear implants in 156 patients with CHARGE syndrome. Temporal bone and facial nerve anomalies were common. Discussion: The assessment and management of patients with CHARGE syndrome undergoing cochlear implantation is challenging. Outcomes may be affected by cochlear nerve deficiency, inner ear anomalies, and developmental delay. Surgery is almost invariably complicated by abnormal anatomy, and increased incidence of complications. Conclusion: A careful, case-by-case assessment of an individual's requirements within a multi-disciplinary setup is essential for achieving the best possible outcome.